1992
DOI: 10.1002/ana.410320719
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in Parkinson's disease: A link between oxidative stress and mitochondrial damage?

Abstract: Several links exist between the two mechanisms of neuronal degeneration (i.e., oxygen radical production and mitochondrial damage) proposed to have a role in Parkinson's disease. Indeed, mitochondria are critical targets for the toxic injury induced by oxygen radicals, and experimental evidence suggests that mitochondrial damage may cause an increased generation of oxygen radicals. A potentially important link between these two mechanisms of neurodegeneration is glutathione. Because of the scavenging activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 27 publications
2
54
0
Order By: Relevance
“…It has been proposed that the downregulation of GSH observed in PD is associated with mitochondrial damage caused by oxidative stress and that this decrease in GSH accelerates the death of dopaminergic neurons (26). Consistent with this finding, we found that depletion of Pink1 in lymphocytes via shRNA treatment led to a dramatic decrease in GSH that sensitized T cells to death caused by IL-2 withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…It has been proposed that the downregulation of GSH observed in PD is associated with mitochondrial damage caused by oxidative stress and that this decrease in GSH accelerates the death of dopaminergic neurons (26). Consistent with this finding, we found that depletion of Pink1 in lymphocytes via shRNA treatment led to a dramatic decrease in GSH that sensitized T cells to death caused by IL-2 withdrawal.…”
Section: Discussionsupporting
confidence: 90%
“…Instead the duration of exposure to an oxidized GSH/GSSG ratio was critical for inactivation. These changes in complex I activity are of considerable pathological significance as the selective loss of complex I activity in the substantia nigra of brains from Parkinson's disease patients is associated with oxidation of the glutathione pool (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its action as a redox coupled proton pump, complex I is a major source of ROS within the cell (49), is involved in the mitochondrial permeability transition (50), is particularly susceptible to inactivation during degenerative diseases and other pathologies (47,48) and is also involved in early mitochondrial changes during apoptosis (51). The central role of complex I in mitochondria suggests that the Grx2-catalyzed glutathionylation of complex I in response to slight oxidation of the mitochondrial glutathione pool may have physiological significance.…”
Section: Discussionmentioning
confidence: 99%
“…Complex I was markedly more susceptible to glutathionylation and irreversible inactivation than other respiratory chain complexes. This may explain why complex I is selectively damaged in Parkinson's disease or Huntington's disease (16,17,47) and indicates why mitochondrial oxidative stress and glutathione depletion are common features of these diseases (48,49). Redox active complex I thiols also reacted with S-nitroso compounds, probably by transnitrosation to form S-nitrosothiols.…”
Section: Formation Of Complex I Protein-glutathione Mixed Disulfides mentioning
confidence: 99%